Revenge and psychological adjustment after homicidal loss. Issue 6 (6th June 2014) - van Denderen, Mariëtte; de Keijser, Jos; Gerlsma, Coby; Huisman, Mark; Boelen, Paul A.
<x xml:space="preserve">Abstract</x> Feelings of revenge are a common human response to being hurt by others. Among crime victims of severe sexual or physical violence, significant correlations have been reported between revenge and Posttraumatic Stress Disorder (PTSD). Homicide is one of the most severe forms of interpersonal violence. It is therefore likely that individuals bereaved by homicide experience high levels of revenge, which may hamper efforts to cope with traumatic loss. The relationship between revenge and psychological adjustment following homicidal loss has not yet been empirically examined. In the current cross‐sectional study, we used self‐report data from 331 spouses, family members and friends of homicide victims to examine the relationships between dispositional revenge and situational revenge on the one hand and symptom‐levels of PTSD and complicated grief, as well as indices of positive functioning, on the other hand. Furthermore, the association between revenge and socio‐demographic and offense‐related factors was examined. Participants were recruited from a governmental support organization, a website with information for homicidally bereaved individuals, and members of support groups. Levels of both dispositional and situational revenge were positively associated with symptoms of PTSD and complicated grief, and negatively with positive functioning. Participants reported significantly less situational revenge in cases where the perpetrator was a direct family member than cases where the perpetrator was an indirect family member, friend, or someone unknown. Homicidally bereaved individuals reported more situational revenge, but not more dispositional revenge than a sample of students who had experienced relatively mild interpersonal transgressions. Aggr. Behav. 40:504–511, 2014. © 2014 Wiley Periodicals, Inc.